Pleural effusion related to IgG4. Issue 4 (July 2019) - Murata, Yoriyuki; Aoe, Keisuke; Mimura, Yusuke
Abstract : Purpose of review: The causes of exudative pleural effusions are diverse and frequently remain unclear despite exhaustive examinations. Recently recognized IgG4-related disease (IgG4-RD) is a fibroinflammatory disorder that can affect nearly any organ including the lungs. This review will focus on the involvement of IgG4 in exudative pleural effusion of unknown cause. Recent findings: IgG4 is found to be involved in a proportion of patients with undiagnosed pleural effusions. Pleural involvement in IgG4-RD can be seen in isolation or association with other organ disease. Pleural thickening and/or effusion are common clinical features of IgG4-related pleural lesions, and this condition is histologically characterized by a lymphoplasmacytic infiltrate enriched in IgG4-positive plasma cells in the pleura. Although the pathogenesis of IgG4-RD is poorly understood, there is a growing body of evidence that indicates an antigen-driven process requiring T-cell and B-cell interaction in which autoantibodies, plasmablasts, follicular helper T cells and CD4+ cytotoxic T lymphocytes participate. Summary: The possibility of IgG4-related pleural lesion should be considered in patients with pleural effusion of unexplained cause when lymphoplasmacytic infiltration is seen in a pleural biopsy specimen. This condition is responsive to systemic steroid therapy.